Operational Innovation: Efforts to Achieve Company Competitive Advantage - Imam Wibowo (Sean Institute, 2023)
The speed of technological development and dynamic market changes have encouraged companies to continue to innovate to maintain their competitiveness. This research aims to examine the role of operational innovation to achieve a company's competitive advantage in the operational management concept. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of operational innovation by focusing on the introduction of new ideas, integration of solutions with existing processes, and gradual change management has a positive impact on organizational performance. Involving team members in identifying obstacles and finding solutions as well as tracking progress by setting performance benchmarks and KPIs has proven to be effective. By adopting this strategy, organizations can improve operational efficiency, respond quickly to market changes, and create a strong foundation for sustainable growth, making a positive contribution to competitiveness and long-term sustainability.